The recovery of homicidal people diagnosed with schizophrenia and schizoaffective disorder—An interpretative phenomenological analysis - Kovács, Asztrik; Ladányi, Bence; Farkas, Noémi; Stempel, Laura; Kiss, Dániel; Bittermann, Évi; Rácz, József (Frontiers in Psychiatry, 2023)
Objective Identity recovery in people diagnosed with schizophrenia who have committed homicide poses several difficulties. Premorbid mental illnesses, the experience of psychosis, and the absence of cohesive ego functions may result in the inability to integrate the homicidal act into self-identity. Problems with integration increase the risk of recidivism and further mental problems. The aim of the present research was to explore how homicidal people diagnosed with schizophrenia make sense of their actions, and how they identify with the homicide. Method Six semi-structured interviews were conducted at a long-term psychiatric home with people who had committed homicide and who had been diagnosed with schizophrenia. The interviews were transcribed verbatim and analysed using interpretative phenomenological analysis (IPA), an idiographic method rooted in phenomenologist traditions that focuses on how participants experience and make sense of events in their lives, and how those events affect their identity and sense of self. Results Three personal experiential themes were established as a result of the analysis: (1) homicide and responsibility; (2) homicide and self; and (3) control over threats to self and self-evaluation. (1) Homicide was often reported to have been committed in a non-conscious, delusional state that may have led to the loss of self-determination. (2) Our interviewees struggled to integrate their acts into their identities. They distanced themselves from the crime or held multiple, parallel interpretations of the act. (3) Recovering patients experienced the constant threat of entering into a delusional reality and losing control. The importance of control was central to their self-evaluation. The patients appeared to distance themselves from the homicidal act and to regard their delusional selves as a threat to their lives. Conclusion Therapy aimed at bolstering self-control, supporting the integration of the fragmented self, and raising awareness of the connections between delusional reality and standard, intersubjective reality may be helpful in reducing the instability of the self. Therapy aimed at processing complex grief and loss of family is also needed.